(untitled) (Texas Journal of Engineering and Technology, 2022)
In the research work carried out, the efficiency of the capture of fine-particle Dust, which is thrown into the atmosphere from the production of industrial enterprises, was achieved by the practical application of the energy-efficient mesh structural dust capture equipment. This equipment is installed as a second-step dust catcher in the production workshops. Increased efficiency in the capture of small dust particles that are not completely cleaned in production cexes is important. With this, it is achieved that the amount of dust flow inside and outside the territory of the enterprise does not exceed the permissible amount of air content (REM)and improves the state of the environment